Exploring the societal views towards ASD and its impact on the quality of life of ASD individuals in Malaysia - Kor, Belle Ming Hui; Chua, Hui Qin; Imran, Mohammad Azlan (2022)
Problems such as isolation, stigmatization and unemployment have troubled the quality of life(QoL) of those with Autism Spectrum Disorder (ASD), these problems are connected with thesociety’s perception of ASD individuals. This research explores the societal views towards thoseliving with ASD and the impact of it on their QoL. Semi structured one-on-one interviews with 5ASD individuals are used to focus on the individual impact from ASD individuals, whilepurposive sampling method was used. What was founded was the isolation and the poor QoLfrom ASD individuals because of societal views, aligning with previous research, howeverparticipants also exhibit healthy and positive coping mechanisms, not aligning with previousresearch. The findings verify how societal views affect those with ASD negatively but also howthose with ASD do not cope as dependently as assumed. The research implication can expand theknowledge of ASD and gives material to spread accurate information of ASD. It can also be usedas a basis for future research and filling in research gaps by providing a more in depth look of theMalaysian context. However, caution is needed as the narrow demographic of sample population,homogeneousness of ASD functional level and single source perspective limits the research. Toconclude, there is an impact of societal views of ASD towards the treatment of ASD such asisolation and poor QoL, however coping wise was positive, with this it provides implications tohelp spread knowledge of ASD and fill in research gaps.